2015
DOI: 10.1111/jph.12395
|View full text |Cite
|
Sign up to set email alerts
|

Precise Disease Severity Assessment for False Smut Disease of Rice

Abstract: False smut is a disease of rice inflorescence. The existing systems of disease severity assessment for rice false smut disease are not very sensitive as the ball quality and also the impact of false smut on filled grain number and grain‐filling were not under consideration. Here, a precise assessment method to evaluate the severity of the disease was developed. The ‘yield representative’ (YR) based on ‘mean floret wt.’ and ‘filled grain %’ was simulated for the precise disease severity assessment of rice false… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
(20 reference statements)
2
9
0
Order By: Relevance
“…Similar results were presented in the data provided by Nessa et al (2015). Dhua et al (2015) also observed that small false smut balls (average ball weight of less than 40 mg) tended to be produced in tolerant rice cultivars. It will be interesting to address the underlying mechanism in the future.…”
Section: Host Responses To Vv Infectionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were presented in the data provided by Nessa et al (2015). Dhua et al (2015) also observed that small false smut balls (average ball weight of less than 40 mg) tended to be produced in tolerant rice cultivars. It will be interesting to address the underlying mechanism in the future.…”
Section: Host Responses To Vv Infectionsupporting
confidence: 87%
“…We speculate that Vv may hijack the host nutrient reservoir by mimicking fertilization and activating the grain‐filling network, extracting nutrients towards colonization sites for growth and for the formation of false smut balls. Consistent with this hypothesis, a recent study has shown that mild Vv infection (one to two false smut balls per diseased panicle) can enhance rice yield attributes, such as the filled grain number and grain weight (Dhua et al ., ). Similar results were presented in the data provided by Nessa et al .…”
Section: Molecular Vv–rice Interactionsmentioning
confidence: 97%
“…This finding is further supported by an independent study [63]. Although the underlying mechanism needs further investigation, the observation of V. virens activating rice grain filling could provide a promising explanation why mild V. virens infection enhances rice yield traits, including grain weight and filled grain number [9]. Identification and characterization of V. virens factors that manipulate rice grain filling should be an interesting research area in the future.…”
Section: Host Compatible Interaction With V Virenssupporting
confidence: 55%
“…The disease induces considerable losses both in yield and quality [7,8], due to the occurrence of RFS balls and increased sterility of kernels adjacent to the balls [9]. Moreover, RFS balls produce two types of mycotoxins, i.e., ustiloxin and ustilaginoidin, which are poisonous to both humans and animals and impose significant health hazards by contaminating rice grains and straws [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…U. virens specifically infects rice flowers and develops into large mycelial colonies covered with massive chlamydospores, called false smut balls (Tang et al, 2013;Fan et al, 2016). Formation of false smut balls not only leads to considerable yield losses but also generates a diversity of mycotoxins poisonous to humans and animals (Zhou et al, 2012;Dhua et al, 2015). U. virensproduced mycotoxins mainly include ustiloxins and ustilaginoidins, which show cytotoxicities and phytotoxicities by inhibiting the mitosis process in eukaryotic cells (Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%